Perlawanan diskursif terhadap mimpi Amerika dalam novel American Dirt karya Jeanine Cummins - Kasih, E. Ngestirosa Endang Woro; Indriyanto, Kristiawan; Surtinawati, Surtinawati; Nabila, Meri (Universitas Mulawarman, 2025)
This research aims to examine the discursive discourse on the American dream in the novel American Dirt by Jeanine Cummins. This novel tells the life of Lydia and her son, Luca as immigrants in the United States. This study uses a qualitative descriptive method supported by Stuart Hall’s represnetation theory and belonging theory. The narrative of Mexican immigrants built by Cummins illustrates the ideals of achieving the American dream for a better life in the existing characters. However, the life that is dreamed of does not go completely as it should. Lydia and Luca are trying to achieve their ideal goals as new citizens. However, minority construction is still a hindrance. With the theory of representation and belonging, the depiction of Lydia and Luca’s lives is a process that immigrants should face. The rejection of the majority by the minority is an ongoing negotiation process and is not easy to achieve. Lydia and Luca are representations of Mexican immigrants who still have to negotiate the search for identity in a new community in the United States.